A synthetic phase-contrast imaging diagnostic with spatial filtering for gyrokinetic simulations. (1st February 2023) - Iantchenko, A; Coda, S; Brunner, S; Merlo, G; Ball, J; Margairaz, F
Abstract: A Phase-contrast imaging (PCI) diagnostic provides measurements of line-integrated electron density fluctuations. Localisation along the laser beam path can be achieved with a spatial filter that selects the wave-vector directions of the fluctuations contributing to the PCI measurement and is a key feature of the PCI diagnostic installed on the TCV tokamak and also of a similar system planned for JT-60SA. We have developed a synthetic diagnostic that models measurements from PCI taking into account the effect of such a spatial filter. The synthetic tool is based on the principle of integrating over selected diagnostic volumes the electron density fluctuations generated by turbulence simulations, and applying an appropriate spatial filter in wave-vector space. We demonstrate the effect of the filter for a positive and a negative triangularity TCV discharge, and illustrate the potential of the synthetic diagnostic for better understanding the corresponding experimental results. We consider different types of filters and make first-principle estimates of the localisation of the measurement. Finally, using gyrokinetic simulations that include electromagnetic effects, collisions and four kinetic species, we make first predictions of the characteristics of the measurements using the planned set-up of PCI on JT-60SA.